Toxicity and toxin properties of puffer fish collected from Kuching coastal waters - Shareena Nazlia, binti Mohd Azhar (Universiti Malaysia Sarawak, UNIMAS, 2012)
This study was carried out to determine the toxicity level and toxin properties of puffer fish which are Tetraodon nigroviridis, Xenopterus naritus and Lagocephalus lunaris. A total of 52 samples of puffer fish were collected from Telaga Air and Muara Tebas. The sample was caught by using gill net and trawl net. The morphology and physical measurement including total length, standard length, body weight, pectoral fin, anal fin, dorsal fin and caudal fin were observed, counted and recorded. Toxin analysis had been carried out by using thin layer chromatography (TLC) in 1-butanol:acetic acid:water solvent (12:3:5) and by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Toxin has been extracted from muscle, liver, skin, egg and gonad. The TLC screening result shows that, the Rf value were varies from 0.10-0.57 and some of the sample tissue gave a Rf value that similar to authentic tetrodotoxin (TTX) standard, 0.20. LC-MS/MS were used to verify and determine the amount of TTX. Based on the result, the toxicity level (MU/g) were calculated in the range of 7.41-1804.03 where the highest amount of TTX were in egg followed by gonad, liver, muscle and skin. As an conclusion, TTX exhibited in T. nigroviridis, X. naritus and L. lunaris in Kuching coastal.